Job Crafting Influences Work Engagement Through The Mediation Of Organizational Trust Among Healthcare Workers - Septin Maisharah Karyono; Tulus Winarsunu; Nida Hasanati (Care : Jurnal Ilmiah Ilmu Kesehatan, 2026)
Healthcare workers frequently experience high workloads, emotional demands, and organizational pressures that may reduce work engagement. Although job crafting has been associated with positive work outcomes, the mechanism through which organizational trust influences this relationship remains insufficiently understood, particularly in healthcare settings. This cross-sectional study was conducted at X Hospital Surabaya between 2 March 2026 and 12 March 2026. The study involved healthcare workers (nurses, doctors, and midwives) selected using purposive sampling. Data were collected using validated questionnaires measuring job crafting, organizational trust, and work engagement. Structural Equation Modeling Partial Least Squares (SEM-PLS) with 5,000 bootstrap resamples were generated to analyze the data. Job crafting significantly influenced organizational trust (?=0.585; p0.001). Organizational trust significantly influenced work engagement (?=0.725; p0.001). However, the direct effect of job crafting on work engagement was not significant (?=0.035; p=0.649). The indirect effect through organizational trust was significant (?=0.424; p0.001), indicating full mediation. Organizational trust fully mediates the relationship between job crafting and work engagement. Strengthening organizational trust is essential for translating proactive work behaviors into sustainable engagement among healthcare workers